The religious crisis of the 1960s - McLeod, Hugh. (Oxford ; New York : Oxford University Press, 2007)
The 1960s were a time of explosive change and innovation in the Christian churches, as well as of charismatic leaders like Pope John XXIII and Martin Luther King. Using oral history, Hugh McLeod explains what happened to religion in the 1960s, why it happened, and how the events of that decade shaped the rest of the 20th century.
Includes bibliographical references (p. [266]-282) and index.
Description based on print version record.
Keywords: Church history -- 20th century; Religion -- History -- 20th century; RELIGION -- Christianity -- Pentecostal & Charismatic; Electronic books; Church history -- 20th century; Church history; Religion -- History -- 20th century; Religion